2015
DOI: 10.1002/mds.26326
|View full text |Cite
|
Sign up to set email alerts
|

Eltoprazine prevents levodopa‐induced dyskinesias by reducing striatal glutamate and direct pathway activity

Abstract: Eltoprazine inhibits the sensitization of striatonigral medium-sized GABA spiny neurons (the direct pathway) to L-dopa and their overactivation associated with dyskinesias appearance. Activation of 5-HT1A and 5-HT1B receptors regulating striatal glutamate transmission, but not striatal ectopic dopamine release, might underlie the symptomatic effect of eltoprazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 70 publications
1
67
0
Order By: Relevance
“…In these days, various approaches using 5-HT 1A agonists target mainly motor fluctuation in PD [138-142, 161-167] (Table 1). Eltoprazine, a selective 5-HT 1A and 5-HT 1B agonist, is currently being tested in clinical trials for motor complications derived from dopaminergic therapy in PD [140, 141].…”
Section: Serotonin 1a (5-ht1a) Receptors On Astrocytes As a Novel Tarmentioning
confidence: 99%
“…In these days, various approaches using 5-HT 1A agonists target mainly motor fluctuation in PD [138-142, 161-167] (Table 1). Eltoprazine, a selective 5-HT 1A and 5-HT 1B agonist, is currently being tested in clinical trials for motor complications derived from dopaminergic therapy in PD [140, 141].…”
Section: Serotonin 1a (5-ht1a) Receptors On Astrocytes As a Novel Tarmentioning
confidence: 99%
“…11 Therefore, increased GLT-1 and glutamate uptake may reduce LID severity by reducing excess glutamatergic neurotransmission, as seen with observations showing reduced LID in association with reduced glutamate release. 49,50 To the converse, others have not reported any difference in striatal glutamate concentrations in the lesioned nigrostriatal pathway, 10,74,75 which may be attributed to timedependent changes in release and uptake and their contributions to extracellular glutamate concentration and when these determinations were made after lesion induction or the lesion site. 4,5,40,75 As a result, postlesion time points and lesion topography are relevant metrics for timing therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…35,47,48 The pharmacological-based reduction of striatal or nigral glutamate efflux may reduce LID severity. [49][50][51] GLT-1 is a primary glial glutamate transporter responsible for clearing synaptic glutamate 52 and may be involved in neurodegenerative processes. 11,[15][16][17][18] Ceftriaxone, a beta-lactam antibiotic, can increase GLT-1 expression with >5 consecutive daily injections.…”
mentioning
confidence: 99%
“…In stress-induced hyperthermia test, eltoprazine failed to demonstrate any effect (Zethof et al 1995), a finding somewhat contradictory to the results of the present study, where dose-dependent hypothermia was observed. Eltoprazine also abolished stress-induced ultrasonic vocalization in adult rats (Sanchez 1993) Eltoprazine produced dose-dependent hypothermia with a minimal effective dose of 1 mg/kg, which seems to be within range decreasing weight gain but slightly higher than doses reported to exert antidyskinetic effects (0.3 mg/kg) (Paolone et al 2015). Hyperthermic activity of 5-HT1A ligands seems to correlate with the potency and the intrinsic activity at the 5-HT1A receptor (Millan et al 1993).…”
Section: Discussionmentioning
confidence: 99%